The leadership challenge in the Immigration Division of the Department of Home Affairs - Macharavanda, Patience Immaculate (My University, 2016)
Over the past twenty years and even during the apartheid era, South Africa has undergone significant waves of migration and leadership challenges. Migration into South Africa has been, and still is, a result of many different factors that include economic reasons and seeking political refuge. This migration wave has also taken its toll on the country’s leadership skills and strategies as well as the Immigration Department as regards the issuance of legal documents to migrants to be able to stay legally in the country. Leadership is usually revered in Africa, but this places pressure to perform well on the country’s existing leadership in relation to the control of migration and the maintenance of peace within the borders of the country. The study aimed to identify whether the leadership is performing the way it is supposed to perform. Is the leadership performing with character and competence and are they taking responsibility for their actions when dealing with the public as this matter affects the public sector. Statistics South Africa has an estimate of number of the migrants flowing into the country and the Department of Home Affairs does not have an accurate number of the migration flow, due to the daily rapid movement at the border posts. It is known, however, that the number of migrants into the country has increased and continues to increase, and this poses a challenge for the leadership. One of the recommendations that emerged from the findings of the study is that more programmes and workshops should be undertaken to equip the civil servants in the Department of Home Affairs as they are all leaders in various ways and are also representatives of the Department. Their conduct should therefore be professional as they represent the image of South Africa.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits School of Governance, 2016
Keywords: Public administration--South Africa; Leadership--South Africa